1959
DOI: 10.1099/00221287-20-3-634
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Typing Pattern of Phage-Type 80 Staphylococci

Abstract: SUMMARY : Three temperate phages isolated from lysogenic staphylococci of phage type 52/52A/80 were used to lysogenize strains of phage-type 80. Two of these phages belonged to serological group A and one to serological group F. Lysogenization of a strain of phage-type 80 with one of the phages (287') resulted in a change in the typing pattern from 80/81 to 52/52A/80. There was, therefore, a gain in sensitivity to phage 52 and 52A and a loss in sensitivity to phage 81. Lysogenization of type 80 strains with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

1960
1960
1986
1986

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(23 citation statements)
references
References 5 publications
0
23
0
Order By: Relevance
“…It was shown previously [2,15] that changes in phage typing pattern in staphylococci resulted from artificial lysogenization. It was reported by Asheshov and Rippon [1] and by Rountree [32] that certain changes in phage typing patterns which follow artificial lysogenization are the results of serologically specific prophage immunity. The phage typing pattern of type 80/81 strains was reported to be changed to 52/52A/80/81 after lysogenization by certain serological group A phages.…”
Section: Genetic Features Of Drug Resistance and Phage Type In S Aureusmentioning
confidence: 99%
“…It was shown previously [2,15] that changes in phage typing pattern in staphylococci resulted from artificial lysogenization. It was reported by Asheshov and Rippon [1] and by Rountree [32] that certain changes in phage typing patterns which follow artificial lysogenization are the results of serologically specific prophage immunity. The phage typing pattern of type 80/81 strains was reported to be changed to 52/52A/80/81 after lysogenization by certain serological group A phages.…”
Section: Genetic Features Of Drug Resistance and Phage Type In S Aureusmentioning
confidence: 99%
“…The general similarity of the phage group I isolates would not originally have caused problems since the strains were isolated from different wards or in different years. Asheshov & Rippon (1959) Naidoo, 1984).…”
Section: Discussionmentioning
confidence: 99%
“…They were as follows: strain 594, isolated from the same patient as strain 590 and presumed to have been converted from strain 590 in vivo. Lysogenic clones of this strain were used as the source of two converting phages and are described in detail below; strain 6346 DL, derived from strain 6346 which was lysogenized with a converting phage, 7287l, and subsequently cured (Asheshov & Rippon, 1959). This strain is believed to be completely non-lysogenic; strain 80 la, a mutant of P.S.…”
Section: Methodsmentioning
confidence: 99%
“…It seemed, therefore, that phage b might have its origin in a hitherto undetected prophage in P.S. 80 or else be a recombinant of such a hypothetical prophage with the phage a or a. Lysogenicity of type 80181 strains Previous attempts to demonstrate lysogenicity in type sol81 strains had been unsuccessful (Asheshov & Rippon, 1959;Rountree, 1959) but the appearance of phage b during the growth of phage a and n in these strains indicated that a further search should be made. When supernatant fluids of 2-4 hr.…”
Section: Phages Isolated From Strain 594mentioning
confidence: 99%